Keep the fate: how chromatin regulators safeguard embryonic stem cell identity. (17th May 2021) - Janiszewski, Adrian; Georgolopoulos, Grigorios; Balli, Martina; Athanasouli, Paraskevi; Lluis, Frederic; Pasque, Vincent
Abstract : Segregation of cells that form the embryo from those that produce the surrounding extra‐embryonic tissues is critical for early mammalian development, but the regulatory layers governing these first cell fate decisions remain poorly understood. Recent work in The EMBO Journal identifies two chromatin regulators, Hdac3 and Dax1, that synergistically restrict the developmental potential of mouse embryonic stem cells and act as a lineage barrier to primitive endoderm formation. Abstract : Recent work reports histone deacetylase Hdac3 and nuclear receptor Dax1 as lineage barriers to primitive endoderm formation.